2002
DOI: 10.1152/ajpheart.00497.2001
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide-induced vasorelaxation in rabbit aortic rings has two components: G protein dependent and independent

Abstract: The endogenous cannabinoid anandamide (arachidonylethanolamide) produces vasorelaxation in different vascular beds. In the present study, we found that anandamide and a metabolically stable analog, methanandamide, produced dose-dependent (10 nM-10 microM) vasorelaxation of approximately 80% in a rabbit aortic ring preparation in an endothelium-dependent manner. Non-endothelium-dependent vasorelaxation was observed to be a maximum of 20-22% at >10 microM methanandamide. The efficacious CB(1) receptor analogs de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
111
4
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 42 publications
11
111
4
1
Order By: Relevance
“…Vascular endothelial cells express CB 1 receptors (28,34,40) as well as SR141716-sensitive receptors distinct from CB 1 or CB 2 (10,41,42). The involvement of these latter receptors is suggested by our observation 2 that the SR141716-sensitive hypotensive response to LPS remains unchanged in CB 1 knockout or CB 1 /CB 2 double knockout mice.…”
Section: Lps-treated Macrophages Elicitmentioning
confidence: 75%
“…Vascular endothelial cells express CB 1 receptors (28,34,40) as well as SR141716-sensitive receptors distinct from CB 1 or CB 2 (10,41,42). The involvement of these latter receptors is suggested by our observation 2 that the SR141716-sensitive hypotensive response to LPS remains unchanged in CB 1 knockout or CB 1 /CB 2 double knockout mice.…”
Section: Lps-treated Macrophages Elicitmentioning
confidence: 75%
“…Anandamide can elicit vasodilation 13,[32][33][34] and decreased cardiac contractility 35 through an additional G i /G o -coupled receptor distinct from CB 1 or CB 2 , which is inhibited by SR141716 13 but not by other CB 1 antagonists such as AM251. 35,36 In the present experiments, AM251 and SR141716 were equally effective in eliciting pressor and cardiostimulatory responses and in blocking the depressor effects of URB597 in hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Abn-cbd elicits endothelium-dependent vasodilation in the isolated mesenteric arterial bed of the rat and mouse, including mice lacking both CB 1 and CB 2 receptors (10). More recently, a study of the responses of isolated segments of rat mesenteric arteries indicated that the endothelium dependent vasorelaxing effect of both anandamide and abd-cbd could be inhibited by another structural analog of cannabidiol, O-1918 (13), as well as by pertussis toxin (13,14), and a similar site has been identified in the rabbit aortic endothelium (15). Vanilloid VR1 receptors, which mediate the endothelium-independent component of the vasodilator effect of anandamide (15,16), do not have a role in this endotheliumdependent vasodilator response (10,(13)(14)(15).…”
mentioning
confidence: 93%
“…More recently, a study of the responses of isolated segments of rat mesenteric arteries indicated that the endothelium dependent vasorelaxing effect of both anandamide and abd-cbd could be inhibited by another structural analog of cannabidiol, O-1918 (13), as well as by pertussis toxin (13,14), and a similar site has been identified in the rabbit aortic endothelium (15). Vanilloid VR1 receptors, which mediate the endothelium-independent component of the vasodilator effect of anandamide (15,16), do not have a role in this endotheliumdependent vasodilator response (10,(13)(14)(15). This has led us to postulate the existence of a novel, endothelial cannabinoid receptor coupled to G i /G o , for which abn-cbd is a selective agonist and O-1918 is a silent antagonist (13).…”
mentioning
confidence: 95%